Propylene-α-olefin copolymer and its uses

By preparing propylene-α-olefin copolymers with specific structures, the problem of insufficient performance of existing copolymers in tensile strength and flexibility is solved, and the copolymers have a good balance in these two aspects and have excellent mechanical properties and processing properties.

JP7657084B2Active Publication Date: 2025-04-04MITSUI CHEMICALS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021055021
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-04-04
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

The existing propylene-α-olefin copolymers are insufficient in tensile strength and flexibility, and it is difficult to achieve a good balance.

Method used

A propylene-α-olefin copolymer is developed with structural units ranging from propylene 75-95 mol% and α-olefin 5-25 mol% and prepared by specific polymerization conditions and catalytic systems such as using crosslinked metal cycloolefin composites and organoaluminum oxides to ensure that the copolymer has low or no melting point, high isotactic ternary components and suitable intrinsic viscosity.

Benefits of technology

The propylene-α-olefin copolymer has achieved a good balance in flexibility and tension strength, and has excellent mechanical properties and processing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657084000001
    Figure 0007657084000001
  • Figure 0007657084000002
    Figure 0007657084000002
  • Figure 0007657084000003
    Figure 0007657084000003
Patent Text Reader

Abstract

To provide a propylene-α-olefin copolymer which has an excellent balance between flexibility and tensile strength.SOLUTION: A propylene-α-olefin copolymer satisfies the following requirements (I) to (IV). (I) When the total of a structural unit (i) derived from propylene and a structural unit (ii) derived from α-olefin having 5 to 20 carbon atoms is 100 mol%, a content of the structural unit (i) is 75-95 mol%, and a content of the structural unit (ii) is 5-25 mol%, (II) a melting point measured by differential scanning calorimetry (DSC) is 95°C or lower or is not observed, (III) an isotactic triad fraction measured by 13C-NMR is 85% or more, and (IV) intrinsic viscosity [η] measured in decalin at 135°C is 0.5-10 dl / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a propylene / α-olefin copolymer, an adhesive resin composition, pellets, a molded article, a film, a sheet, a fiber, an injection molded article, a blow molded article, an automobile part, and a tubular member. [Background technology]

[0002] 2. Description of the Related Art In recent years, propylene-based copolymers containing propylene as a main component have become known as soft polyolefin materials that are excellent in flexibility, heat resistance, and transparency as well as environmental friendliness and hygienic properties.

[0003] At present, while the applications of such propylene-based copolymers are expanding, the performance of the propylene-based copolymers currently in use is insufficient, and there is room for improvement in terms of, for example, tensile strength and flexibility.

[0004] In this regard, Patent Document 1 describes a propylene-ethylene polymer that is somewhat excellent in tensile strength, flexural modulus and elasticity. Patent Document 2 also describes that a composition excellent in flexibility, tensile elongation properties, etc. can be provided by using a propylene-1-butene copolymer having a Shore A hardness of 70 or less, an intrinsic viscosity [η] of 0.3 or more in a xylene solvent at a temperature of 70°C, and having neither a crystalline melting peak nor a crystallization peak. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-049863 A [Patent Document 2] Japanese Patent Application Publication No. 11-193309 Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above-mentioned conventional techniques, the present inventors have conducted extensive research into propylene / α-olefin copolymers and have found that propylene / α-olefin copolymers having HAO (Higher Alpha Olefin) have an excellent balance between flexibility and tensile strength. The present invention has been made in consideration of the above, and an object of the present invention is to provide a propylene-α-olefin copolymer that is excellent in balance between flexibility and tensile strength. [Means for solving the problem]

[0007] A configuration example of the present invention is as follows. In this specification, the numerical range "A to B" indicates A or more and B or less.

[0008] [1] A propylene-α-olefin copolymer satisfying the following requirements (I) to (IV): (I) When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 5 to 20 carbon atoms is taken as 100 mol %, the content of the structural unit (i) is 75 to 95 mol %, and the content of the structural unit (ii) is 5 to 25 mol %. (II) The melting point as measured by differential scanning calorimetry (DSC) is 95°C or less or not observed. (III) 13 The isotactic triad fraction measured by C-NMR is 85% or more. (IV) The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 10 dl / g.

[0009] [2] 13 The propylene / α-olefin copolymer according to [1], having an isotactic triad fraction of 90% or more as measured by C-NMR.

[0010] [3] The propylene / α-olefin copolymer according to [1] or [2], which has a MFR of 0.1 to 30 g / 10 min under a load of 2.16 kg at 230°C, as measured in accordance with ASTM D1238E.

[0011] [4] The propylene / α-olefin copolymer according to any one of [1] to [3], wherein the α-olefin having 5 to 20 carbon atoms is at least one selected from the group consisting of 1-hexene, 1-octene, 1-decene and 1-dodecene. [5] The propylene / α-olefin copolymer according to any one of [1] to [4], wherein the α-olefin having 5 to 20 carbon atoms is 1-octene.

[0012] [6] An adhesive resin composition comprising the propylene / α-olefin copolymer according to any one of [1] to [5]. [7] A pellet comprising the propylene / α-olefin copolymer according to any one of [1] to [5], or the adhesive resin composition according to [6]. [8] A molded article comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6]. [9] A film comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[10] A sheet comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[11] A fiber comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[12] An injection-molded article comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[13] A blow-molded article comprising the propylene / α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[14] An automobile part selected from interior and exterior parts, comprising the propylene-α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6].

[15] A tubular member selected from a pipe and a tube, comprising the propylene-α-olefin copolymer according to any one of [1] to [5] or the adhesive resin composition according to [6]. Effect of the Invention

[0013] According to the present invention, it is possible to provide a propylene-α-olefin copolymer having a good balance between flexibility and tensile strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Propylene-α-olefin copolymer> The propylene / α-olefin copolymer according to the present invention (hereinafter also referred to as “the copolymer”) satisfies the following requirements (I) to (IV). (I) When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 5 to 20 carbon atoms is taken as 100 mol %, the content of the structural unit (i) is 75 to 95 mol %, and the content of the structural unit (ii) is 5 to 25 mol %. (II) The melting point as measured by differential scanning calorimetry (DSC) is 95°C or less or not observed. (III) 13 The isotactic triad fraction (mm fraction) measured by C-NMR is 85% or more. (IV) The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 10 dl / g.

[0015] The present copolymer is not particularly limited as long as it is a copolymer obtained by using propylene and one or more α-olefins having 5 to 20 carbon atoms, but is preferably a random copolymer.

[0016] The content of the structural unit (i) is from 75 to 95 mol %, preferably from 80 to 95 mol %, and more preferably from 85 to 95 mol %. The content of the structural unit (ii) is from 5 to 25 mol %, preferably from 5 to 20 mol %, and more preferably from 5 to 15 mol %. The content of each of the structural units (i) and (ii) is the content when the total of the structural units (i) and (ii) is taken as 100 mol %.

[0017] The copolymer having the content of the structural units (i) and (ii) within the above range tends to have a good balance between flexibility and mechanical strength, and in particular, has a good balance between flexibility and tensile strength. The content of the structural units (i) and (ii) is 13 It can be measured by C-NMR, specifically, by the method described in the examples below.

[0018] Examples of the α-olefin having 5 to 20 carbon atoms include 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. Of these, 1-hexene, 1-octene, and 1-dodecene are preferred, and 1-octene is more preferred, because they can form a crystal structure with many tie molecules and provide a copolymer with a good balance between flexibility and tensile strength. The α-olefins having 5 to 20 carbon atoms may be used in two or more kinds, but preferably in one kind.

[0019] The copolymer has a melting point Tm of 95° C. or lower as measured by DSC, or no melting point is observed as measured by DSC (no melting peak is observed by DSC). When a melting point is observed, Tm is preferably 90° C. or lower, more preferably 85° C. or lower, with no particular lower limit. The present copolymer, which has a melting point within the above range or no observable melting point, has excellent flexibility. The melting point is specifically measured by the method described in the following examples. Here, the melting point refers to the temperature at the peak of the melting peak, and "no melting peak is observed" means that no crystal melting peak with a crystal melting heat (ΔH) of 1 J / g or more is observed in the range of -100 to 200°C. When two or more melting peaks are observed, the highest temperature among the peak peak temperatures of these peaks is the melting point.

[0020] When the melting peak is observed, the heat of fusion (ΔH), which is the integrated value of the peak, is preferably 1 to 50 J / g, more preferably 5 to 45 J / g, and further preferably 10 to 40 J / g. The copolymer having a ΔH within the above range has a good balance between flexibility and low stickiness.

[0021] The mm fraction of the present copolymer is 85% or more, preferably 90% or more, more preferably 92% or more, and particularly preferably 98% or more. The present copolymer having a mm fraction within the above range, and particularly an injection molded article containing the present copolymer, is excellent in balance of flowability, mechanical strength and impact resistance. The mm fraction can be measured and analyzed by the method described in JP-A-2007-186664.

[0022] The intrinsic viscosity [η] of the present copolymer measured in decalin at 135° C. is from 0.5 to 10 dl / g, preferably from 1 to 5 dl / g, and more preferably from 1.5 to 2.5 dl / g. The copolymer having an intrinsic viscosity [η] within the above range has excellent moldability, mechanical strength and low stickiness.

[0023] The MFR of the copolymer measured in accordance with ASTM D1238E at 230° C. under a load of 2.16 kg is preferably from 0.1 to 30 g / 10 min, more preferably from 0.2 to 15 g / 10 min. The copolymer having an MFR in the above range has a good balance of excellent moldability, mechanical strength, and low stickiness.

[0024] The instantaneous Shore A hardness of the copolymer is preferably 25 to 99, more preferably 28 to 98, further preferably 50 to 98, and particularly preferably 60 to 97. When it is difficult to measure the Shore A hardness, the same evaluation can be performed using the Shore D hardness instead. The instantaneous Shore D hardness of the copolymer is preferably 12 to 62, and more preferably 18 to 60. The Shore A hardness (instantaneous value) and the Shore D hardness (instantaneous value) are specifically measured by the method described in the following examples.

[0025] <Method of producing the copolymer> The present copolymer can be suitably produced by a method including a step of polymerizing propylene and at least one olefin selected from α-olefins having 5 to 20 carbon atoms in the presence of an olefin polymerization catalyst described below.

[0026] 1. Olefin polymerization catalysts The olefin polymerization catalyst is preferably a catalyst containing a bridged metallocene compound (A) and at least one compound (B) selected from the following (b-1) to (b-3): (b-1) Organoaluminum oxy compounds (b-2) an ionic compound that reacts with the bridged metallocene compound (A) to form an ion pair (b-3) Organoaluminum compounds

[0027] [Bridged metallocene compound (A)] The bridged metallocene compound (A) is preferably a compound represented by the following formula [A1], and more preferably a compound represented by the following formula [A2]. The bridged metallocene compound (A) may be used alone or in combination of two or more kinds.

[0028] [ka]

[0029] In formula [A1], M is a Group 4 transition metal, such as a titanium atom, a zirconium atom, or a hafnium atom; j is an integer of 1 to 4; Q is selected from a halogen atom, a hydrocarbon group, a neutral conjugated or non-conjugated diene having 10 or less carbon atoms, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair; when j is 2 to 4, multiple Qs may be the same or different; R A and R B are mononuclear or polynuclear hydrocarbon residues which may be the same or different from each other and can form a sandwich structure with M, Y is a carbon atom or a silicon atom, R C and R D may be the same or different and are selected from a hydrogen atom, a hydrocarbon group, a silicon-containing group, a halogen atom and a halogen-containing hydrocarbon group, and may be bonded to each other to form a ring.

[0030] [ka]

[0031] In formula [A2], R 1 is a hydrocarbon group, a silicon-containing group, or a halogen-containing hydrocarbon group; R 2 ~R 10 is selected from a hydrogen atom, a hydrocarbon group, a silicon-containing group, a halogen atom, and a halogen-containing hydrocarbon group, and may be the same or different, and each substituent may be bonded to each other to form a ring. M is a Group 4 transition metal, and j is an integer of 1 to 4. Q is selected from a halogen atom, a hydrocarbon group, a neutral conjugated or non-conjugated diene having 10 or less carbon atoms, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair, and when j is 2 to 4, multiple Qs may be the same or different.

[0032] Among the bridged metallocene compounds represented by formula [A2], the bridged metallocene compounds represented by the following formula [A3] are particularly preferred from the viewpoints of polymerization characteristics, availability, and the ease with which a propylene-α-olefin copolymer satisfying the above requirements can be obtained.

[0033] [ka]

[0034] In formula [A3], R 1b is a hydrocarbon group, a silicon-containing group, or a halogen-containing hydrocarbon group; R 2b ~R 12b is selected from a hydrogen atom, a hydrocarbon group, a silicon-containing group, a halogen atom, and a halogen-containing hydrocarbon group, and may be the same or different, and each substituent may be bonded to each other to form a ring. M is a Group 4 transition metal, n is an integer of 1 to 3, and j is an integer of 1 to 4. Q is selected from a halogen atom, a hydrocarbon group, a neutral conjugated or non-conjugated diene having 10 or less carbon atoms, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair, and when j is 2 to 4, multiple Qs may be the same or different.

[0035] R 1 From R 10 and R 1b From R 12b Examples of the hydrocarbon group in the formula (1) include a linear hydrocarbon group, a branched hydrocarbon group, a cyclic saturated hydrocarbon group, a cyclic unsaturated hydrocarbon group, and a group in which one or more hydrogen atoms of a saturated hydrocarbon group are substituted with a cyclic unsaturated hydrocarbon group. The number of carbon atoms in the hydrocarbon group is usually 1 to 20, preferably 1 to 15, and more preferably 1 to 10.

[0036] Examples of the linear hydrocarbon group include linear alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, and an n-decanyl group; and linear alkenyl groups such as an allyl group.

[0037] Examples of branched hydrocarbon groups include branched alkyl groups such as an isopropyl group, a tert-butyl group, a tert-amyl group, a 3-methylpentyl group, a 1,1-diethylpropyl group, a 1,1-dimethylbutyl group, a 1-methyl-1-propylbutyl group, a 1,1-propylbutyl group, a 1,1-dimethyl-2-methylpropyl group, and a 1-methyl-1-isopropyl-2-methylpropyl group.

[0038] Examples of cyclic saturated hydrocarbon groups include cycloalkyl groups such as a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, and a methylcyclohexyl group; and polycyclic groups such as a norbornyl group, an adamantyl group, and a methyladamantyl group.

[0039] Examples of cyclic unsaturated hydrocarbon groups include aryl groups such as phenyl, tolyl, naphthyl, biphenyl, phenanthryl, and anthracenyl; cycloalkenyl groups such as cyclohexenyl; and polycyclic unsaturated alicyclic groups such as 5-bicyclo[2.2.1]hept-2-enyl.

[0040] Examples of groups in which one or more hydrogen atoms of a saturated hydrocarbon group are substituted with a cyclic unsaturated hydrocarbon group include groups in which one or more hydrogen atoms of an alkyl group, such as a benzyl group, a cumyl group, a 1,1-diphenylethyl group, or a triphenylmethyl group, are substituted with an aryl group.

[0041] R 1 From R 10 and R 1b From R 12b Examples of the silicon-containing group in the formula -SiR include a trimethylsilyl group, a triethylsilyl group, a dimethylphenylsilyl group, a diphenylmethylsilyl group, and a triphenylsilyl group. 3 (wherein each of the multiple R's is independently an alkyl group having 1 to 15 carbon atoms or a phenyl group).

[0042] R 1 From R 10 and R1b From R 12b Examples of the halogen-containing hydrocarbon group in the above formula include groups in which one or more hydrogen atoms of the above hydrocarbon group are substituted with halogen atoms, such as a trifluoromethyl group.

[0043] R 2 From R 10 and R 2b From R 12b Examples of the halogen atom in include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0044] R 2 From R 10 and R 2b From R 12b Of the substituents up to , two substituents (e.g., R 2b and R 3b , R 3b and R 4b , R 5b and R 6b , R 6b and R 7b , R 8b and R 9b , R 9b and R 10b , R 10b and R 11b , R 11b and R 12b ) may be bonded to each other to form a ring, and the ring formation may occur at two or more positions in the molecule.

[0045] In this specification, examples of the ring (spiro ring, additional ring) formed by bonding two substituents to each other include alicyclic ring and aromatic ring.Specific examples include cyclohexane ring, benzene ring, hydrogenated benzene ring, and cyclopentene ring, and preferably cyclohexane ring, benzene ring, and hydrogenated benzene ring.In addition, such a ring structure may further have a substituent such as an alkyl group on the ring.

[0046] R 1bFrom the viewpoint of stereoregularity, is preferably a hydrocarbon group, more preferably a hydrocarbon group having 1 to 20 carbon atoms, still more preferably not an aryl group, particularly preferably a linear hydrocarbon group, a branched hydrocarbon group, or a cyclic saturated hydrocarbon group, and particularly preferably a group in which the carbon having a free valence (the carbon bonded to the cyclopentadienyl ring) is a tertiary carbon.

[0047] R 1b Specific examples of such a substituent include a methyl group, an ethyl group, an isopropyl group, a tert-butyl group, a tert-pentyl group, a tert-amyl group, a 1-methylcyclohexyl group, and a 1-adamantyl group. More preferred are substituents in which the carbon having a free valence is a tertiary carbon, such as a tert-butyl group, a tert-pentyl group, a 1-methylcyclohexyl group, and a 1-adamantyl group. Particularly preferred are a tert-butyl group and a 1-adamantyl group.

[0048] In the formula [A3], the fluorene ring portion is not particularly limited as long as it has a structure obtained from a known fluorene derivative. 4b and R 5b From the viewpoints of stereoregularity and molecular weight, is preferably a hydrogen atom.

[0049] R 2b , R 3b , R 6b and R 7b are preferably hydrogen atoms or hydrocarbon groups, more preferably at least two of them are hydrocarbon groups, and even more preferably at least two of them are hydrocarbon groups having 1 to 20 carbon atoms. 2b and R 3b are bonded to each other to form a ring, and R 6b and R 7b may be bonded to each other to form a ring. Examples of such substituted fluorenyl groups include a benzofluorenyl group, a dibenzofluorenyl group, an octahydrodibenzofluorenyl group, a 1,1,4,4,7,7,10,10-octamethyl-2,3,4,7,8,9,10,12-octahydro-1H-dibenzo[b,h]fluorenyl group, a 1,1,3,3,6,6,8,8-octamethyl-2,3,6,7,8,10 1,1,4,4,7,7,10,10-octamethyl-2,3,4,7,8,9,10,12-octahydro-1H-dibenzo[b,h]fluorenyl group is particularly preferred.

[0050] R 8b is preferably a hydrogen atom or a hydrocarbon group, more preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, and further preferably a hydrogen atom or a methyl group.

[0051] R 9b is more preferably a hydrocarbon group, and R 9b is more preferably an alkyl group having one or more carbon atoms, such as a linear alkyl group or a branched alkyl group, a cycloalkyl group, or a cycloalkenyl group, and R 9b is particularly preferably an alkyl group having one or more carbon atoms.

[0052] From a synthetic point of view, R 10b and R 11b is also preferably a hydrogen atom. Or, when n=1, R 9b and R 10b are more preferably bonded to each other to form a ring, and the ring is particularly preferably a six-membered ring such as a cyclohexane ring. In this case, R 11b is preferably a hydrogen atom.

[0053] R 12b is preferably a hydrocarbon group, and particularly preferably an alkyl group.

[0054] M is a Group 4 transition metal, for example, Ti, Zr or Hf, preferably Zr or Hf, and particularly preferably Zr.

[0055] Q represents a halogen atom, a hydrocarbon group, a neutral conjugated or non-conjugated diene having 10 or less carbon atoms, an anionic ligand, or a neutral ligand capable of coordinating with a lone electron pair.

[0056] Examples of the halogen atom in Q include fluorine, chlorine, bromine, and iodine.

[0057] The hydrocarbon group in Q is preferably an alkyl group having 1 to 10 carbon atoms, or a cycloalkyl group having 3 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an iso-propyl group, a 2-methylpropyl group, a 1,1-dimethylpropyl group, a 2,2-dimethylpropyl group, a 1,1-diethylpropyl group, a 1-ethyl-1-methylpropyl group, a 1,1,2,2-tetramethylpropyl group, a sec-butyl group, a tert-butyl group, a 1,1-dimethylbutyl group, a 1,1,3-trimethylbutyl group, and a neopentyl group; examples of the cycloalkyl group having 3 to 10 carbon atoms include a cyclohexylmethyl group, a cyclohexyl group, and a 1-methyl-1-cyclohexyl group. The number of carbon atoms in the hydrocarbon group is more preferably 5 or less.

[0058] Neutral conjugated or non-conjugated dienes with 10 or less carbon atoms include s-cis- or s-trans-η 4 -1,3-butadiene, s-cis- or s-trans-η 4 -1,4-diphenyl-1,3-butadiene, s-cis- or s-trans-η 4 -3-Methyl-1,3-pentadiene, s-cis- or s-trans-η 4 -1,4-Dibenzyl-1,3-butadiene, s-cis- or s-trans-η 4 -2,4-Hexadiene, s-cis- or s-trans-η 4 -1,3-Pentadiene, s-cis- or s-trans-η4 -1,4-Ditolyl-1,3-butadiene, s-cis- or s-trans-η 4 An example is -1,4-bis(trimethylsilyl)-1,3-butadiene.

[0059] Examples of the anionic ligand include alkoxy groups such as methoxy and tert-butoxy; aryloxy groups such as phenoxy; carboxylate groups such as acetate and benzoate; and sulfonate groups such as mesylate and tosylate.

[0060] Examples of neutral ligands capable of coordinating with lone electron pairs include organic phosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine; and ethers such as tetrahydrofuran (THF), diethyl ether, dioxane, and 1,2-dimethoxyethane.

[0061] A preferred embodiment of Q is a halogen atom or an alkyl group having 1 to 5 carbon atoms.

[0062] n is an integer of 1 to 3, preferably 1 or 2, and more preferably 1. When n is within the above range, the propylene / α-olefin copolymer can be efficiently obtained, which is preferable.

[0063] j is an integer of 1 to 4, and is preferably 2.

[0064] The above describes the structure of the bridged metallocene compound represented by formula [A2] or [A3], i.e., R 1 ~R 10 , R 1b ~R 12b The preferred embodiments of M, n, Q and j have been described above. As the bridged metallocene compound (A), any combination of the preferred embodiments is also a preferred embodiment. Such a bridged metallocene compound can be suitably used to obtain the present copolymer having the above physical properties.

[0065] An example of the bridged metallocene compound represented by the formula [A2] is diphenylmethylene(3-tert-butyl-5-ethylcyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride.

[0066] Examples of the bridged metallocene compound represented by formula [A3] include (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride or the catalyst (b) described in Japanese Patent No. 6568082. Here, the octamethylfluorene refers to 1,1,4,4,7,7,10,10-octamethyl-2,3,4,7,8,9,10,12-octahydro-1H-dibenzo[b,h]fluorene.

[0067] In addition, the bridged metallocene compound represented by the formula [A1] may also be R A and R B may be the same or different, and are a substituted indenyl group, and Y is a silicon atom. Examples of the substituent in the substituted indenyl group include a halogen atom, a hydrocarbon group, a silicon-containing group, and a halogen-containing hydrocarbon group. Specific examples of these include R in the formulae [A2] and [A3]. 1 and R 2 and the like. C , R D and MQ j The R part is explained in the formula [A2] and [A3] columns. 9 , R 10 and MQ j Specific examples of such bridged metallocene compounds include dimethylsilylene-bis{1-(2-n-propyl-4-phenanthryl indenyl)}zirconium dichloride and dimethylsilylene-bis{1-(2-n-propyl-4-phenanthryl indenyl)}hafnium dichloride.

[0068] [Compound (B)] 《Organoaluminum oxy compound (b-1)》 Examples of the organoaluminum oxy compound (b-1) include conventionally known aluminoxanes such as the compound represented by the following formula [B1] and the compound represented by the following formula [B2], a modified methylaluminoxane having a structure represented by the following formula [B3], and a boron-containing organoaluminum oxy compound represented by the following formula [B4]. The organoaluminum oxy compound (b-1) may be used alone or in combination of two or more kinds.

[0069] [ka]

[0070] In formulae [B1] and [B2], R is a hydrocarbon group having 1 to 10 carbon atoms, preferably a methyl group, and a plurality of R may be the same or different. n is an integer of 2 or more, preferably 3 or more, more preferably 10 or more. In formulae [B1] and [B2], methylaluminoxane in which R is a methyl group is preferably used.

[0071] [ka]

[0072] In the formula [B3], Me is a methyl group, R is a hydrocarbon group having 2 to 10 carbon atoms, and m and n are each independently an integer of 2 or more. A plurality of Rs may be the same or different from each other. Modified methylaluminoxane [B3] can be prepared using trimethylaluminum and alkylaluminum other than trimethylaluminum. Such modified methylaluminoxane [B3] is generally called MMAO (modified methyl aluminoxane). MMAO can be prepared by the method described in U.S. Pat. No. 4,960,878 and U.S. Pat. No. 5,041,584, or the like.

[0073] In addition, modified methylaluminoxanes prepared using trimethylaluminum and triisobutylaluminum (i.e., R in formula [B3] is an isobutyl group) are commercially produced by Tosoh Finechem Co., Ltd. and other companies under the trade names MMAO and TMAO.

[0074] MMAO is an aluminoxane with improved solubility in various solvents and improved storage stability. Specifically, unlike compounds insoluble or poorly soluble in benzene, such as the compounds represented by formula [B1] or [B2], MMAO is soluble in aliphatic hydrocarbons, alicyclic hydrocarbons, and aromatic hydrocarbons.

[0075] [ka]

[0076] In formula [B4], R c is a hydrocarbon group having 1 to 10 carbon atoms. d are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 10 carbon atoms. In the production method using the above-mentioned olefin polymerization catalyst, a propylene-α-olefin copolymer can be produced even at high temperatures as described below. Therefore, organoaluminum oxy compounds that are insoluble or poorly soluble in benzene, such as those exemplified in JP-A-2-78687, can also be used. In addition, organoaluminum oxy compounds described in JP-A-2-167305 and aluminoxanes having two or more types of alkyl groups, such as those described in JP-A-3-103407, can also be suitably used.

[0077] The "benzene-insoluble or poorly soluble" organoaluminum oxy-compound refers to an organoaluminum oxy-compound that is insoluble or poorly soluble in benzene, and in which the amount of the compound that dissolves in benzene at 60°C is usually 10% by mass or less, preferably 5% by mass or less, and particularly preferably 2% by mass or less, calculated as Al atoms.

[0078] <Ionic compounds (b-2)> Examples of the compound (b-2) (hereinafter also simply referred to as "ionic compound (b-2)") that reacts with the bridged metallocene compound (A) to form an ion pair include Lewis acids, ionic compounds, borane compounds, and carborane compounds described in JP-T-1-501950, JP-T-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, JP-A-2004-51676, and U.S. Pat. No. 5,321,106. In addition, heteropoly compounds and isopoly compounds are also exemplified. Among these, the compound represented by the following formula [B5] is preferred. The ionic compound (b-2) may be used alone or in combination of two or more kinds.

[0079] [ka]

[0080] In formula [B5], R e+ As for H + Examples of the cation include an oxonium cation, a carbenium cation, an ammonium cation, a phosphonium cation, a cycloheptyltrienyl cation, and a ferrocenium cation having a transition metal. f , R g , R h and R i each independently represents an organic group, and is preferably an aryl group or a halogen-substituted aryl group.

[0081] Examples of the carbenium cation include tri-substituted carbenium cations such as triphenylcarbenium cation, tris(methylphenyl)carbenium cation, and tris(dimethylphenyl)carbenium cation.

[0082] Examples of ammonium cations include trialkylammonium cations such as trimethylammonium cation, triethylammonium cation, tri(n-propyl)ammonium cation, triisopropylammonium cation, tri(n-butyl)ammonium cation, and triisobutylammonium cation; N,N-dialkylanilinium cations such as N,N-dimethylanilinium cation, N,N-diethylanilinium cation, and N,N,2,4,6-pentamethylanilinium cation; and dialkylammonium cations such as diisopropylammonium cation and dicyclohexylammonium cation.

[0083] Examples of the phosphonium cation include triarylphosphonium cations such as triphenylphosphonium cation, tris(methylphenyl)phosphonium cation, and tris(dimethylphenyl)phosphonium cation.

[0084] R e+ Among the above examples, preferred are carbenium cation and ammonium cation, and particularly preferred are triphenylcarbenium cation, N,N-dimethylanilinium cation and N,N-diethylanilinium cation.

[0085] ·R e+ When is a carbenium cation (carbenium salt) Examples of the carbenium salt include triphenylcarbenium tetraphenylborate, triphenylcarbenium tetrakis(pentafluorophenyl)borate, triphenylcarbenium tetrakis(3,5-ditrifluoromethylphenyl)borate, tris(4-methylphenyl)carbenium tetrakis(pentafluorophenyl)borate, and tris(3,5-dimethylphenyl)carbenium tetrakis(pentafluorophenyl)borate.

[0086] ·R e+ is an ammonium cation (ammonium salt) Examples of the ammonium salt include trialkylammonium salts, N,N-dialkylanilinium salts, and dialkylammonium salts.

[0087] Specific examples of trialkylammonium salts include triethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, tri(n-butyl)ammonium tetraphenylborate, trimethylammonium tetrakis(p-tolyl)borate, trimethylammonium tetrakis(o-tolyl)borate, tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, tripropylammonium tetrakis(pentafluorophenyl)borate, tripropylammonium tetrakis(2,4-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis(3,5-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis(4-trifluoromethylphenyl)borate, tri( Examples of the borate include (n-butyl)ammonium tetrakis(3,5-ditrifluoromethylphenyl)borate, (o-tolyl)tri(n-butyl)ammonium tetrakis(o-tolyl)borate, (dioctadecylmethylammonium tetraphenylborate), (dioctadecylmethylammonium tetrakis(p-tolyl)borate, (dioctadecylmethylammonium tetrakis(o-tolyl)borate, (dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate, (dioctadecylmethylammonium tetrakis(2,4-dimethylphenyl)borate, (dioctadecylmethylammonium tetrakis(3,5-dimethylphenyl)borate, (dioctadecylmethylammonium tetrakis(4-trifluoromethylphenyl)borate, and (dioctadecylmethylammonium tetrakis(3,5-ditrifluoromethylphenyl)borate.

[0088] Examples of the N,N-dialkylanilinium salt include N,N-dimethylanilinium tetraphenylborate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N-diethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N,2,4,6-pentamethylanilinium tetraphenylborate, and N,N,2,4,6-pentamethylanilinium tetrakis(pentafluorophenyl)borate.

[0089] Examples of the dialkylammonium salt include diisopropylammonium tetrakis(pentafluorophenyl)borate and dicyclohexylammonium tetraphenylborate.

[0090] 《Organic Aluminum Compound (b-3)》 Examples of the organic aluminum compound (b-3) include the organic aluminum compound represented by the following formula [B6] and the complex alkylated product of a Group 1 metal of the periodic table and aluminum represented by the following formula [B7]. The organic aluminum compound (b-3) may be used alone or in combination of two or more.

[0091] R a m Al(OR b ) n H p X q ···[B6] In formula [B6], each of R a and R b is independently a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms, X is a halogen atom, m is a number where 0 < m ≦ 3, n is a number where 0 ≦ n < 3, p is a number where 0 ≦ p < 3, q is a number where 0 ≦ q < 3, and m + n + p + q = 3.

[0092] M2 AlR a 4 [B7] In formula [B7], M 2 is Li, Na or K, and there are multiple R a are each independently a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms.

[0093] Examples of the organoaluminum compound [B6] include tri-n-alkylaluminums such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, trihexylaluminum, and trioctylaluminum; tri-branched alkylaluminums such as triisopropylaluminum, triisobutylaluminum, trisec-butylaluminum, tritert-butylaluminum, tri-2-methylbutylaluminum, tri-3-methylhexylaluminum, and tri-2-ethylhexylaluminum; tricycloalkylaluminums such as tricyclohexylaluminum and tricyclooctylaluminum; triarylaluminums such as triphenylaluminum and tritolylaluminum; 4 H 9 ) x Al y (C 5 H 10 ) z (wherein x, y and z are positive numbers, and z≦2x); alkylaluminum alkoxides such as isobutylaluminum methoxide and isobutylaluminum ethoxide; dialkylaluminum alkoxides such as dimethylaluminum methoxide, diethylaluminum ethoxide and dibutylaluminum butoxide; alkylaluminum sesquialkoxides such as ethylaluminum sesquiethoxide and butylaluminum sesquibutoxide; a 2.5 Al(OR b ) 0.5 (In the formula, R a and R b is R in formula [B6] a and R bis synonymous with. dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, dibutylaluminum chloride, diethylaluminum bromide, diisobutylaluminum chloride; alkylaluminum sesquihalides such as ethylaluminum sesquichloride, butylaluminum sesquichloride, ethylaluminum sesquibromide; partially halogenated alkylaluminums such as alkylaluminum dihalides such as ethylaluminum dichloride; dialkylaluminum hydrides such as diethylaluminum hydride, dibutylaluminum hydride, diisopropylaluminum hydride, diisobutylaluminum hydride; partially hydrogenated alkylaluminums such as alkylaluminum dihydrides such as ethylaluminum dihydride, propylaluminum dihydride; and partially alkoxylated and halogenated alkylaluminums such as ethylaluminum ethoxy chloride, butylaluminum butoxy chloride, ethylaluminum ethoxy bromide.

[0094] The alkylated complex [B7] is LiAl(C 2 H 5 ) 4 , LiAl(C 7 H 15 ) 4 In addition, compounds similar to the alkyl complex [B7] can also be used, specifically, organoaluminum compounds in which two or more aluminum compounds are bonded via nitrogen atoms. Examples of such compounds include (C 2 H 5 ) 2 AlN(C 2 H 5 )Al(C 2 H 5 ) 2 Examples include:

[0095] As the organoaluminum compound (b-3), trimethylaluminum and triisobutylaluminum are preferred from the viewpoint of easy availability.

[0096] [Carrier (C)] A support (C) may be used as a component of the olefin polymerization catalyst. The support (C) is preferably an inorganic or organic compound that is a granular or fine particle solid. The carrier (C) may be used alone or in combination of two or more kinds.

[0097] 《Inorganic compounds》 Examples of inorganic compounds include porous oxides, inorganic halides, clay minerals, clay (usually composed mainly of clay minerals), and ion-exchangeable layered compounds (most clay minerals are ion-exchangeable layered compounds).

[0098] Porous oxides include SiO 2 , Al 2 O 3 , MgO, ZrO, TiO 2 , B 2 O 3 , CaO, ZnO, BaO, ThO 2 Examples of the composites or mixtures containing these oxides include natural or synthetic zeolites, SiO 2 -MgO, SiO 2 -Al 2 O 3 , SiO 2 -TiO 2 , SiO 2 -V 2 O 5 , SiO 2 -Cr 2 O 3 , SiO 2 -TiO 2 Among these, SiO 2 and Al 2 O 3 A porous oxide containing either one or both of the above as main components is preferred.

[0099] The properties of the porous oxide vary depending on the type and manufacturing method, but the particle size is preferably in the range of 10 to 300 μm, more preferably 20 to 200 μm; the specific surface area is preferably in the range of 50 to 1000 m 2 / g, more preferably 100 to 700m 2 / g; the pore volume is preferably in the range of 0.3 to 3.0 cm 3 / g. Such a porous oxide is calcined, for example, at 100 to 1000° C., preferably 150 to 700° C., as required, before use.

[0100] Inorganic halides include MgCl 2 , MgBr 2 , MnCl 2 , MnBr 2 The inorganic halide may be used as it is, or may be used after being pulverized by a ball mill, a vibration mill, etc. Also, the inorganic halide may be dissolved in a solvent such as alcohol, and then the component precipitated in the form of fine particles by a precipitating agent may be used.

[0101] Clay, clay minerals, and ion-exchangeable layered compounds are not limited to natural products, and artificially synthesized products can also be used. Note that ion-exchangeable layered compounds are compounds having a crystal structure in which planes formed by ionic bonds or the like are stacked in parallel with each other with weak bonding forces, and the ions contained therein are exchangeable.

[0102] Specific examples of clays and clay minerals include kaolin, bentonite, kibushi clay, gairome clay, allophane, hisingerite, pyrophyllite, synthetic mica and other mica group, montmorillonite group, vermiculite, ryokudeite group, palygorskite, kaolinite, nacrite, dickite, hectorite, taeniolite, and halloysite.

[0103] It is also preferable to subject the clay or clay mineral to a chemical treatment. As the chemical treatment, any of surface treatments for removing impurities adhering to the surface and treatments for affecting the crystal structure of the clay can be used. Specific examples of the chemical treatment include acid treatment, alkali treatment, salt treatment, and organic matter treatment.

[0104] Ion-exchangeable layered compounds include hexagonal close-packed type, antimony type, CdCl 2 Type, CdI 2 Examples of ion-exchangeable layered compounds include α-Zr(HAsO 4 ) 2 H 2 O, α-Zr(HPO 4 ) 2 , α-Zr(KPO 4 ) 2 3H 2 O, α-Ti(HPO 4 ) 2 , α-Ti(HAsO 4 ) 2 H 2 O, α-Sn(HPO 4 ) 2 H 2 O, γ-Zr(HPO 4 ) 2 , γ-Ti(HPO 4 ) 2 , γ-Ti(NH 4 PO 4 ) 2 H 2 Examples include crystalline acid salts of polyvalent metals such as O.

[0105] In addition, the ion-exchangeable layered compound may be made into a layered compound with an expanded space between layers by exchanging the exchangeable ions between layers with other large bulky ions by utilizing its ion exchangeability. Such bulky ions play a role of pillars supporting the layered structure, and are usually called pillars. For example, oxide pillars can be formed between layers by intercalating the following metal hydroxide ions between layers of the layered compound and then dehydrating them by heating. The introduction of another substance between layers of the layered compound in this way is called intercalation.

[0106] The intercalating guest compound is TiCl 4 , ZrCl 4 Cationic inorganic compounds such as Ti(OR) 4 , Zr(OR) 4 , PO(OR) 3 , B(OR) 3 Metal alkoxides such as (R is a hydrocarbon group, etc.); [Al 13 O 4 (OH) 24 ] 7+ , [Zr 4 (OH) 14 ] 2+ , [Fe 3 O(OCOCH 3 ) 6 ] + These guest compounds may be used alone or in combination of two or more.

[0107] In addition, when the guest compound is intercalated, Si(OR) 4 , Al(OR) 3 , Ge(OR) 4 Polymers obtained by hydrolysis and polycondensation of metal alkoxides (R is a hydrocarbon group, etc.) such as SiO 2 Colloidal inorganic compounds such as the above may also be present.

[0108] Among the inorganic compounds, clay minerals and clays are preferred, with the montmorillonite group, vermiculite, hectorite, taeniolite and synthetic mica being particularly preferred.

[0109] 《Organic compounds》 Examples of organic compounds include granular or particulate solids with particle sizes in the range of 10 to 300 μm.Specific examples include (co)polymers synthesized mainly from ethylene and an α-olefin having 3 to 20 carbon atoms; (co)polymers synthesized mainly from vinylcyclohexane and styrene; and modified products of these (co)polymers.

[0110] [Organic compound component (D)] An organic compound component (D) may be used as a component of the olefin polymerization catalyst. The organic compound component (D) is used, as necessary, for the purpose of improving the polymerization performance in the polymerization reaction of α-olefins and the physical properties of the resulting copolymer. Examples of the organic compound component (D) include alcohols, phenolic compounds, carboxylic acids, phosphorus compounds, and sulfonates. The organic compound component (D) may be used alone or in combination of two or more kinds.

[0111] [Olefin polymerization catalyst composition] When olefins are polymerized using an olefin polymerization catalyst, the amounts of each component that may constitute the olefin polymerization catalyst are as follows, or are preferably set as follows.

[0112] (1) When olefin polymerization is carried out using an olefin polymerization catalyst, the bridged metallocene compound (A) is usually used in an amount of 10 -9 ~10 -1 Molar, preferably 10 -8 ~10 -2 It is used in molar amounts.

[0113] (2) When an organoaluminum oxy compound (b-1) is used as a component of an olefin polymerization catalyst, the compound (b-1) is used in such an amount that the molar ratio [Al / M] of the aluminum atom (Al) in the compound (b-1) to the total transition metal atoms (M) in the bridged metallocene compound (A) is usually 0.01 to 5000, preferably 0.05 to 2000.

[0114] (3) When an ionic compound (b-2) is used as a component of an olefin polymerization catalyst, the compound (b-2) is used in such an amount that the molar ratio of the compound (b-2) to the total transition metal atoms (M) in the bridged metallocene compound (A), [(b-2) / M], is usually 1 to 10, preferably 1 to 5.

[0115] (4) When an organoaluminum compound (b-3) is used as a component of an olefin polymerization catalyst, the compound (b-3) is used in such an amount that the molar ratio of the compound (b-3) to the total transition metal atoms (M) in the bridged metallocene compound (A), [(b-3) / M], is usually 10 to 5,000, preferably 20 to 2,000.

[0116] (5) When an organic compound component (D) is used as a component of an olefin polymerization catalyst, when compound (B) is an organoaluminum oxy compound (b-1), the molar ratio of the organic compound component (D) to the compound (b-1) [(D) / (b-1)] is usually 0.01 to 10, preferably 0.1 to 5; when compound (B) is an ionic compound (b-2), the molar ratio of the organic compound component (D) to the compound (b-2) [(D) / (b-2)] is usually 0.01 to 10, preferably 0.1 to 5; when compound (B) is an organoaluminum compound (b-3), the molar ratio of the organic compound component (D) to the compound (b-3) [(D) / (b-3)] is usually 0.01 to 2, preferably 0.005 to 1.

[0117] 2.Polymerization method In the production of the present copolymer, the polymerization can be carried out by either a liquid phase polymerization method such as solution polymerization or suspension polymerization, or a gas phase polymerization method.

[0118] In the liquid phase polymerization method, it is preferable to use an inert hydrocarbon medium, and examples of the inert hydrocarbon medium include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane. The inert hydrocarbon medium may be used alone or in combination with two or more kinds. In addition, the so-called bulk polymerization method may be used in which the liquefied olefin itself that can be supplied to the polymerization is used as a solvent.

[0119] The polymerization temperature is usually -50 to +200°C, preferably 0 to +180°C; the polymerization pressure is usually normal pressure to 10 MPa gauge pressure, preferably normal pressure to 5 MPa gauge pressure. The polymerization reaction can be carried out by any of batch, semi-continuous and continuous methods. Furthermore, the polymerization can be carried out in two or more stages with different reaction conditions. The molecular weight of the obtained present copolymer can be adjusted by making hydrogen or the like present in the polymerization system, changing the polymerization temperature, or by the amount of compound (B) used.

[0120] When producing the present copolymer, it is possible to produce the present copolymer having high stereoregularity while maintaining high catalytic activity even under high temperature conditions advantageous for industrial production. Such high temperature conditions include conditions in which the polymerization temperature is usually 40° C. or higher, preferably 40 to 200° C., more preferably 45 to 150° C., and particularly preferably 50 to 150° C. (in other words, particularly preferred are temperatures that can be industrialized).

[0121] In producing the present copolymer, the use of hydrogen in particular is preferable since it can have the effect of improving the polymerization activity of the catalyst and the effect of increasing or decreasing the molecular weight of the resulting polymer. When hydrogen is added to the polymerization system, the amount is appropriately about 0.00001 to 100 NL per mole of olefin. The hydrogen concentration in the polymerization system can be adjusted not only by adjusting the amount of hydrogen supplied, but also by carrying out a reaction that produces or consumes hydrogen within the polymerization system, by separating hydrogen using a membrane, or by releasing a portion of the gas containing hydrogen out of the system.

[0122] In producing the present copolymer, after synthesis by the above-mentioned method, known post-treatment steps such as a catalyst deactivation step, a catalyst residue removal step, a drying step and the like may be carried out as necessary.

[0123] ≪Adhesive resin composition≫ The adhesive resin composition according to the present invention contains the present copolymer. The content of the present copolymer in the adhesive resin composition is preferably 1 to 50% by mass, and more preferably 1 to 40% by mass.

[0124] It is preferable that the adhesive resin composition contains a modified polyolefin, since this has better adhesion and compatibility with the substrate (other resin) and may further improve the wettability of the surface of the resulting molded article. Specific examples of the modified polyolefin include those obtained by graft-modifying the present copolymer with one or more polar monomers.

[0125] Suitable examples of the polar monomer include unsaturated carboxylic acids and / or derivatives thereof, such as unsaturated compounds having one or more carboxylic acid groups, esters of unsaturated carboxylic compounds having a carboxylic acid group and alkyl alcohols, and unsaturated compounds having one or more carboxylic acid anhydride groups (e.g., acid anhydrides of unsaturated dicarboxylic acids). Examples of the unsaturated moiety in these compounds include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The polar monomer is preferably an unsaturated dicarboxylic acid or an acid anhydride thereof, and more preferably maleic acid, nadic acid or an acid anhydride thereof.

[0126] The modification amount (graft amount of polar monomer) in the modified polyolefin is usually 0.1 mass% or more, preferably 0.2 mass% or more, relative to 100 mass% of the modified polyolefin, in order to obtain better adhesion and compatibility with the substrate (other resin), and is usually 50 mass% or less, preferably 30 mass% or less, and more preferably 10 mass% or less. The degree of modification can be controlled, for example, by appropriately selecting grafting conditions.

[0127] The method for grafting the polar monomer is not particularly limited, and any conventionally known graft polymerization method can be used, such as a solution method, a melt kneading method, etc. Specifically, for example, the present copolymer is melted or dissolved in a solvent to prepare a solution, and a graft monomer is added thereto to carry out a graft reaction.

[0128] When the modified polyolefin is blended in the adhesive resin composition, the content of the modified polyolefin is preferably 40 to 90 mass %, more preferably 40 to 80 mass %, relative to 100 mass % of the adhesive resin composition. When the content of the modified polyolefin is within the above range, a composition exhibiting high adhesive strength can be easily obtained.

[0129] The adhesive resin composition is usually laminated on one or both sides of a single-layer or multi-layer substrate to form a multilayer film. Specifically, the adhesive resin composition is laminated to form a multilayer film by a method of co-extruding the adhesive resin composition and a substrate layer by a known multilayer film forming method such as a T-die film forming method or an inflation film forming method, or by providing the adhesive resin composition on a substrate previously formed.

[0130] The substrate is not particularly limited, but is preferably a substrate made of a thermoplastic resin. Examples of the thermoplastic resin include polypropylene-based resins (e.g., homopolypropylene, copolymers of propylene and a small amount of α-olefin), polyethylene-based resins (e.g., low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene), known ethylene-based polymers (e.g., ethylene-α-olefin copolymers, ethylene-ethyl acrylate copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl methacrylate copolymers, ethylene-n-butyl acrylate copolymers, ethylene-vinyl alcohol copolymers), poly-4-methyl-pentene-1, and mixtures thereof. The substrate may be surface-treated by a conventional method, and may be colored or printed.

[0131] The multilayer film can be suitably used as a surface protection film for protecting metal plates such as aluminum plates, steel plates, and stainless steel plates, and their coated plates, glass plates, synthetic resin plates, and other processing members, as well as home appliances, automobile parts, and electronic parts using these members.Specific examples of the multilayer film can be suitably used as a film used in the electronics field, such as an optical plate protection film, a lens protection film, a backgrinding tape for semiconductor wafers, a dicing tape, and a protective tape for printed circuit boards, a window glass protection film, and a baking paint film.

[0132] The adhesive resin composition may contain additives other than the present copolymer, specifically, additives such as polyolefins other than the present copolymer or modified products thereof, weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents (crystal nucleating agents), lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, and antioxidants, as necessary, within the scope of the invention. These additives may be used either individually or in combination of two or more.

[0133] For example, a crystal nucleating agent may be used from the viewpoints of increasing the crystallization rate, shortening the molding cycle, increasing transparency, and adjusting rigidity. The crystal nucleating agent is preferably a substance having a nucleating effect on the propylene-based resin, and specific examples include metal salts of aromatic carboxylates, metal salts of aromatic phosphates, alditol derivatives, and metal salts of rosin.

[0134] The aromatic carboxylate metal salt is preferably pt-butylbenzoic acid aluminum. The aromatic phosphate metal salt is preferably 2,2'-methylenebis(4,6-di-t-butylphenyl)sodium phosphate or 2,2'-methylenebis(4,6-di-t-butylphenyl)aluminum phosphate. The alditol derivative is preferably a hexitol derivative or a nonitol derivative, and among them, p-methyl-benzylidene sorbitol, p-ethyl-benzylidene sorbitol, and 7,8,9-trideoxy-3,5:4,6-bis-O-[(4-propylphenyl)methylene]-D-glycero-L-gulo-nonitol are preferably used. When a crystal nucleating agent is used, the content of the crystal nucleating agent in the adhesive resin composition is usually 0.01 to 2% by mass, and preferably 0.05 to 1% by mass.

[0135] The adhesive resin composition can be prepared by mixing the components to be blended in the composition by various known methods, for example, by mixing them with a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender, a kneader-ruder, etc., or by melt-kneading them with a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. Furthermore, granulation, pulverization, etc. may be performed as necessary. When mixing or kneading these components, each component may be added at once or in stages.

[0136] <Pellet> The pellet according to the present invention contains the present copolymer or the adhesive resin composition. The shape, size, etc. of the pellets are not particularly limited and may be appropriately selected depending on the desired application. The pellets can be produced by melting the present copolymer or the adhesive resin composition in a kneader such as a Banbury mixer, a roll or an extruder, and granulating the melted mixture.

[0137] <Molded body> The molded article according to the present invention contains the present copolymer or the adhesive resin composition. The molded article can be produced by molding the copolymer or the adhesive resin composition according to a conventional molding method, for example, a sheet (film) molding method, a blow molding method, a injection molding method, a press molding method, an extrusion molding method, an inflation molding method, an extrusion blow molding method, an injection blow molding method, a vacuum molding method, a calendar molding method, or a melt T-die casting method.

[0138] The molded article is not particularly limited, but since the present copolymer and the adhesive resin composition exhibit the above-mentioned effects, a molded article in which the effects can be more fully exhibited is preferable. Specific examples of the molded article include films, sheets, fibers, injection molded articles, blow molded articles, automobile parts (e.g., automobile interior parts, automobile exterior parts), and cylindrical members (e.g., pipes, tubes). More specific examples include civil engineering and building material parts such as multi-layer hoses, pipes, tubes, decorative sheets, and flooring mats, covering materials for electric wires and cables (e.g., insulating layers, sheath layers), nonwoven fabrics, stretch films, food packaging films, packaging sheets, food packaging trays and beverage cups (obtained by thermoforming the sheet), and plastic containers (obtained by folding the sheet).

[0139] <Film> The film is not particularly limited, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The film may be a stretched film or a non-stretched film, and the film may be a single layer or a multilayer. When the film is a multilayer, at least one layer of the film may be a film containing the present copolymer or the adhesive resin composition.

[0140] The thickness of the film (total thickness if multi-layered) is preferably 5 to 150 μm, more preferably 10 to 100 μm. In this specification, no particular distinction is made between film and sheet, but a film usually refers to a membranous body having a thickness of less than 250 μm, and a sheet usually refers to a thin plate-like body having a thickness of 250 μm or more.

[0141] Specific applications of the film include, for example, packaging films for packaging food, liquids, medicines, and the like.

[0142] <Sheet> The sheet is not particularly limited, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The sheet may be a single layer or a multilayer. When the sheet is a multilayer, at least one layer of the sheet may contain the present copolymer or the adhesive resin composition.

[0143] The thickness of the sheet (if it is multi-layered, the total thickness) is preferably 250 to 2000 μm, more preferably 250 to 1500 μm.

[0144] Specific uses of the sheet include, for example, packaging sheets for packaging food, liquids, medicines, etc., and containers formed from the sheet (e.g., trays, cups, and containers formed by folding the sheet).

[0145] <Textile> The fiber is not particularly limited, and the fiber diameter, fiber length, etc. may be appropriately selected depending on the desired application. The fiber may be one fiber or two or more fibers. When there are two or more fibers, the fiber may be a yarn in which a plurality of the fibers are twisted together. When there are two or more fibers, at least one of them may be a fiber containing the present copolymer or the adhesive resin composition. The fibers can be formed, for example, by melt spinning the copolymer or the adhesive resin composition.

[0146] The fineness of the fibers can be appropriately selected depending on the desired application, etc., but is preferably 0.3 denier or more and less than 10 denier, and more preferably 0.3 denier or more and less than 5 denier.

[0147] Specific applications of the fibers include, for example, nonwoven fabrics and filters.

[0148] <Injection molded products and blow molded products> The injection molded article is not particularly limited, and examples thereof include molded articles produced by injection molding into a desired shape using a conventionally known injection molding device under known conditions. The injection molded articles can be used in a wide range of applications, such as interior trim materials for automobiles, exterior parts for automobiles, housings for home appliances, containers, tubes, pipes, and the like.

[0149] The blow molded article is not particularly limited, and examples thereof include molded articles produced by blow molding into a desired shape using a conventionally known blow molding device under known conditions. The blow molded article may be a multi-layered article, in which case at least one layer contains the present copolymer or the adhesive resin composition.

[0150] Specific applications of the injection molded articles and blow molded articles include, for example, food containers, beverage containers, caps, pharmaceutical containers, various other containers, daily necessities (e.g., clothing cases, buckets, washbasins, stationery such as writing utensils, containers, toys, cooking utensils, and various other cases), housings for home appliances, automobile parts, tubes, and pipes.

[0151] <Automobile interior and exterior parts> The automobile interior and exterior parts are not particularly limited, and examples thereof include automobile parts molded by injection molding or the like. Specific examples of the automobile interior parts include trim, instrument panels, and column covers, while specific examples of the automobile exterior parts include fenders, bumpers, side moldings, mudguards, and mirror covers.

[0152] <Pipes and tubes> The pipes and tubes are not particularly limited, and examples thereof include pipes and tubes molded by injection molding, extrusion molding, etc. The diameter, length, etc. of the pipes and tubes are not particularly limited, and may be appropriately selected depending on the desired application. Specific examples of the pipes and tubes include pipes and tubes used for plumbing or medical purposes. EXAMPLES

[0153] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0154] [Example 1] Preparation of propylene-α-olefin copolymer (β-1) Into a 950 mL continuous polymerization reactor that had been thoroughly purged with nitrogen, dry hexane was fed at a rate of 1,891 mL / hr from one feed inlet, and 1-octene was fed at a rate of 265 mL / hr and a hexane solution of triisobutylaluminum (4.0 mmol / L) was fed at a rate of 49 mL / hr from another feed inlet. At the same time, propylene was supplied at a rate of 1080 mL / hr from another supply port of the continuous polymerization reactor, hydrogen was supplied at a rate of 0.25 NL / hr, and a hexane solution (0.03 mmol / L, zirconium / methylaluminoxane=1 / 300 mol ratio) of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene)) zirconium dichloride (hereinafter also referred to as "catalyst a") synthesized according to Synthesis Example 4 of Japanese Patent No. 5980339 in contact with methylaluminoxane (manufactured by Tosoh Finechem Co., Ltd.) was supplied at a rate of 43 mL / hr into the polymerization reactor, and continuous solution polymerization was carried out under the conditions of a polymerization temperature of 65°C, a total pressure of 3.6 MPaG, a residence time of 17 min, and a stirring speed of 700 rpm. Then, a methanol / hexane solution (methanol / hexane = 2 / 98 volume ratio) was added at a rate of 100 mL / hr to terminate the polymerization. The mixture was then dried at 180 °C under a nitrogen atmosphere for 30 minutes and then dried under vacuum for 30 minutes to produce propylene-α-olefin copolymer (β-1) at a production rate of 150 g / hr.

[0155] [Example 2] Preparation of propylene-α-olefin copolymer (β-2) Propylene-α-olefin copolymer (β-2) was produced in the same manner as in Example 1, except that the feed rate of dry hexane was changed to 1807 mL / hr, the feed rate of 1-octene to 355 mL / hr, the concentration and feed rate of the hexane solution of triisobutylaluminum to 4.5 mmol / L and 57 mL / hr, respectively, the feed rate of hydrogen to 0.19 NL / hr, and the feed rate of the hexane solution in contact with catalyst a and methylaluminoxane to 60 mL / hr.

[0156] [Example 3] Preparation of propylene-α-olefin copolymer (β-3) Propylene-α-olefin copolymer (β-3) was produced in the same manner as in Example 1, except that the feed rates of dry hexane, 1-octene, triisobutylaluminum hexane solution, hydrogen, and hexane solution in contact with catalyst a and methylaluminoxane were changed to 1,718 mL / hr, 440 mL / hr, 61 mL / hr, 0.15 Nl / hr, and 52 mL / hr, respectively.

[0157] [Example 4] Preparation of propylene-α-olefin copolymer (β-4) A propylene-α-olefin copolymer (β-4) was produced in the same manner as in Example 1, except that the feed rate of the hexane solution of triisobutylaluminum was changed to 98 mL / hr, the feed rate of hydrogen was changed to 0.15 Nl / hr, the feed rate of the hexane solution in which catalyst a had been in contact with methylaluminoxane was changed to 82 mL / hr, and the polymerization temperature was changed to 75°C.

[0158] [Example 5] Preparation of propylene-α-olefin copolymer (β-5) A propylene-α-olefin copolymer (β-5) was produced in the same manner as in Example 1, except that the feed rates of dry hexane, 1-octene, and 255 mL / hr, the concentration and feed rate of the hexane solution of triisobutylaluminum were 9 mmol / L and 83 mL / hr, respectively, the hydrogen feed rate was 0.04 Nl / hr, the concentration and feed rate of the hexane solution in contact with catalyst a and methylaluminoxane were 0.06 mol / L and 84 mL / hr, respectively, the polymerization temperature was 85°C, and the residence time was 16 min.

[0159] [Example 6] Preparation of propylene-α-olefin copolymer (β-6) A propylene-α-olefin copolymer (β-6) was produced in the same manner as in Example 1, except that the supply rate of the hexane solution of triisobutylaluminum was changed to 80 mL / hr, the supply rate of hydrogen was changed to 0.1 Nl / hr, and the supply rate of the hexane solution in which catalyst a had been in contact with methylaluminoxane was changed to 69 mL / hr.

[0160] [Example 7] Preparation of propylene-α-olefin copolymer (β-7) Dry hexane was supplied from one supply port of a 950 mL continuous polymerization vessel that had been thoroughly purged with nitrogen at a rate of 2056 mL / hr, and 1-octene was supplied from another supply port at a rate of 375 mL / hr. A hexane solution (0.05 mmol / L, zirconium / methylaluminoxane / triisobutylaluminum=1 / 250 / 200 molar ratio) of diphenylmethylene(3-tert-butyl-5-ethylcyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride (hereinafter also referred to as "catalyst b") synthesized according to Synthesis Example 4 of WO 2006 / 025540 in contact with methylaluminoxane and triisobutylaluminum was supplied into the polymerization vessel at a rate of 72 mL / hr. At the same time, propylene was fed at a rate of 1340mL / hr and hydrogen at a rate of 0.03NL / hr from another feed port of the continuous polymerization reactor, and continuous solution polymerization was carried out under the conditions of polymerization temperature 65°C, total pressure 3.6MPaG, residence time 15min, and stirring speed 700rpm. Then, a methanol / hexane solution (methanol / hexane = 2 / 98 volume ratio) was added at a rate of 100mL / hr to terminate the polymerization. Next, the mixture was dried for 30 minutes under a nitrogen atmosphere at 180°C and then dried for 30 minutes under vacuum, producing propylene-α-olefin copolymer (β-7) at a production rate of 180g / hr.

[0161] [Example 8] Preparation of propylene-α-olefin copolymer (β-8) A propylene-α-olefin copolymer (β-8) was produced in the same manner as in Example 7, except that the feed rates of dry hexane, 1-octene, and the hexane solution in which catalyst b, methylaluminoxane, and triisobutylaluminum had been contacted were changed to 1,852 mL / hr, 585 mL / hr, and 82 mL / hr, respectively.

[0162] [Example 9] Preparation of propylene-α-olefin copolymer (β-9) Propylene-α-olefin copolymer (β-9) was produced in the same manner as in Example 7, except that the feed rates of dry hexane, 1-octene, and the hexane solution in which catalyst b, methylaluminoxane, and triisobutylaluminum were contacted were changed to 1737 mL / hr, 695 mL / hr, and 101 mL / hr, respectively.

[0163] [Example 10] Preparation of propylene-α-olefin copolymer (β-10) Propylene-α-olefin copolymer (β-10) was produced in the same manner as in Example 7, except that the feed rates of dry hexane, 1-octene, propylene, hydrogen, polymerization temperature, and residence time were changed to 1552 mL / hr, 395 mL / hr, 1300 mL / hr, 74°C, and 17 min, respectively.

[0164] [Example 11] Preparation of propylene-α-olefin copolymer (β-11) A propylene-α-olefin copolymer (β-11) was produced in the same manner as in Example 7, except that the feed rates of dry hexane, 1-octene, and the hexane solution in which catalyst b, methylaluminoxane, and triisobutylaluminum were contacted were changed to 1675 mL / hr, 765 mL / hr, and 102 mL / hr, respectively.

[0165] [Example 12] Preparation of propylene-α-olefin copolymer (β-12) A propylene-α-olefin copolymer (β-12) was produced in the same manner as in Example 7, except that the feed rates of dry hexane, 1-octene, and hexane solution in which catalyst b, methylaluminoxane, and triisobutylaluminum were in contact with each other were changed to 1405 mL / hr, 1035 mL / hr, and 103 mL / hr, respectively, and the polymerization temperature was changed to 60°C.

[0166] [Example 13] Preparation of propylene-α-olefin copolymer (β-13) Into a 950 mL continuous polymerization reactor that had been thoroughly purged with nitrogen, dry hexane was fed at a rate of 1,718 mL / hr from one feed port, and 1-octene was fed at a rate of 320 mL / hr and a hexane solution of triisobutylaluminum (4.5 mmol / L) was fed at a rate of 68 mL / hr from another feed port. At the same time, propylene was fed at a rate of 1180 mL / hr, hydrogen at a rate of 0.04 NL / hr, and a hexane solution (0.05 mmol / L, zirconium / methylaluminoxane = 1 / 300 molar ratio) in which a metallocene catalyst (hereinafter also referred to as "catalyst c") represented by the following formula, synthesized according to Synthesis Example 2 of Japanese Patent No. 6568082, and methylaluminoxane were contacted was fed into the polymerization vessel at a rate of 44 mL / hr from another feed port of the continuous polymerization vessel, and continuous solution polymerization was carried out under the conditions of polymerization temperature 65 ° C, total pressure 3.6 MPaG, residence time 17 min, and stirring speed 700 rpm. Thereafter, a methanol / hexane solution (methanol / hexane = 2 / 98 volume ratio) was added at a rate of 100 mL / hr to terminate the polymerization. The mixture was then dried at 180°C for 30 minutes in a nitrogen atmosphere and then dried under vacuum for 30 minutes to produce propylene-α-olefin copolymer (β-13) at a production speed of 187 g / hr.

[0167] [ka]

[0168] [Example 14] Preparation of propylene-α-olefin copolymer (β-14) A propylene-α-olefin copolymer (β-14) was produced in the same manner as in Example 13, except that the feed rate of dry hexane was changed to 1506 mL / hr, the feed rate of 1-octene to 560 mL / hr, the concentration and feed rate of the hexane solution of triisobutylaluminum to 7.5 mmol / L and 60 mL / hr, respectively, and the feed rate of the hexane solution in contact with catalyst c and methylaluminoxane to 55 mL / hr.

[0169] [Comparative Example 1] In Comparative Example 1, a propylene-ethylene copolymer manufactured by ExxonMobil Chemical Corporation (trade name: Vistamaxx3980, MFR (230°C, 2.16 kg load) = 8 g / 10 min) was used.

[0170] [Comparative Example 2] In Comparative Example 2, a propylene-ethylene copolymer manufactured by ExxonMobil Chemical Corporation (trade name: Vistamaxx3000, MFR (230°C, 2.16 kg load) = 7 g / 10 min) was used.

[0171] <Properties of propylene-α-olefin copolymer> The physical properties of the propylene / α-olefin copolymers obtained in the examples and the propylene / α-olefin copolymers used in the comparative examples were measured by the following methods. The results are shown in Table 1.

[0172] a) Propylene and α-olefin content The propylene and α-olefin contents in propylene-α-olefin copolymers are 13 C-NMR measurement was performed, and the obtained 13 It was calculated by analyzing the C-NMR spectrum. In this specification, the content of structural units derived from α-olefins is also referred to as the “α-olefin content”. Equipment: Bruker Biospin AVANCEIIIcryo-500 nuclear magnetic resonance spectrometer Measurement nuclei: 13 C(125MHz) Measurement mode: Single pulse proton broadband decoupling Pulse width: 45° (5.00μsec) Number of points: 64k Measurement range: 250 ppm (-55 to 195 ppm) Repeat time: 5.5 seconds Number of times accumulated: 64 Measurement solvent: orthodichlorobenzene / benzene-d 6 (4 / 1[v / v]) Sample concentration: ca. 60mg / 0.6mL Measurement temperature: 120℃ Window function: exponential (BF: 1.0Hz) Chemical shift standard: CH 3 (P)mmmm signal (21.59ppm)

[0173] b) Isotactic triad fraction (mm fraction) Orthodichlorobenzene / benzene-d 6 (4 / 1[v / v]) solution (CH 3 (P)mmmm signal: 21.59 ppm (reference) 13 C-NMR measurement was performed, and the obtained 13 The ratio (%) of the area of ​​the peak appearing between 21.0 and 22.2 ppm to the total area (100%) of the peaks appearing between 19.2 and 22.2 ppm in the C-NMR spectrum was calculated, and the ratio (%) of the area of ​​the peak was defined as the mm fraction.

[0174] c) MFR The MFR of propylene-α-olefin copolymer was measured at 230℃ under a load of 2.16 kg according to ASTM D1238E.

[0175] d) Intrinsic viscosity [η] The intrinsic viscosity [η] of propylene·α-olefin copolymers was measured at 135°C using decalin as a solvent.

[0176] e) Melting point Tm, heat of fusion ΔH Using a hydraulic hot press molding machine set at 200°C, the propylene-α-olefin copolymer was heated for 6 minutes, molded under a pressure of 10 MPa for 2 minutes, and then cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet (test piece) with a thickness of 500 μm. After 72 hours at room temperature from molding, a test piece of about 10 mg was cooled from 20°C to -20°C at a rate of 10°C / min under a nitrogen atmosphere and held at that temperature for 5 minutes. It was then heated to 200°C at a rate of 10°C / min and held at that temperature for 10 minutes, cooled to -100°C at a rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a rate of 10°C / min. The heat of fusion ΔH was calculated from the integrated value of the crystal melting peak when the temperature was raised for the first time. The melting point Tm was taken as the temperature of the peak apex of the crystal melting peak when the temperature was raised for the second time. When two or more melting peaks were observed, the highest temperature among the peak apex temperatures of these peaks was taken as the melting point. When the heat of fusion ΔH and the melting point Tm were not observed, it was indicated as "ND".

[0177] f) Tensile modulus, breaking stress Using a hydraulic hot press molding machine set at 200°C, the propylene-α-olefin copolymer was heated for 6 minutes, molded for 2 minutes under a pressure of 10 MPa, and then cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet with a thickness of 2 mm. After 72 hours at room temperature from molding, 5A-type dumbbells as specified in JIS K 7161-2:2014 were made from the obtained sheet in accordance with ASTM D638, and the tensile modulus and breaking stress of the dumbbells were measured under conditions of 23°C and a tensile speed of 50 mm / min.

[0178] g) Shore A hardness (instantaneous value) Using a hydraulic hot press molding machine set at 200°C, the propylene-α-olefin copolymer was heated for 6 minutes, molded for 2 minutes under a pressure of 10 MPa, and then cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet with a thickness of 2 mm. After 72 hours had elapsed at room temperature from molding, a durometer hardness tester (Type A) was used, and the scale was read immediately after the indenter was brought into contact with a test piece consisting of three stacked sheets (in accordance with ASTM D2240).

[0179] h) Shore D hardness (instantaneous value) Using a hydraulic hot press molding machine set at 200°C, the propylene-α-olefin copolymer was heated for 6 minutes, molded for 2 minutes under a pressure of 10 MPa, and then cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet with a thickness of 2 mm. After 72 hours had elapsed at room temperature from molding, a durometer hardness tester (D type) was used, and the scale was read immediately after the indenter was brought into contact with a test piece consisting of three stacked sheets (in accordance with ASTM D2240).

[0180] [Table 1]

Claims

1. A propylene / α-olefin copolymer satisfying the following requirements (I) to (IV): (I) When the total of the structural unit (i) derived from propylene and the structural unit (ii) derived from an α-olefin having 5 to 20 carbon atoms is taken as 100 mol %, the content of the structural unit (i) is 75 to 95 mol %, and the content of the structural unit (ii) is 5 to 25 mol %. (II) Using differential scanning calorimetry (DSC), in a nitrogen atmosphere, the sample is cooled from 20°C to -20°C at a temperature drop rate of 10°C / min, held at that temperature for 5 minutes, then heated to 200°C at a temperature increase rate of 10°C / min, held at that temperature for 10 minutes, cooled to -100°C at a temperature drop rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a temperature increase rate of 10°C / min. The melting point, which is the temperature at the apex of the crystal melting peak when the sample is heated for the second time (however, when two or more melting peaks are observed, the highest temperature among the temperatures at the apex of these peaks is the melting point), is 95°C or less or is not observed. (III) orthodichlorobenzene / benzene-d 6 (4 / 1 [v / v]) solution (CH 3 (P) mmmm signal: 21.59 ppm as reference) 13 The isotactic triad fraction measured by C-NMR is 85% or more. (IV) The intrinsic viscosity [η] measured in decalin at 135° C. is 1 to 2.5 dl / g.

2. 13 2. The propylene / α-olefin copolymer according to claim 1, having an isotactic triad fraction of 90% or more as measured by C-NMR.

3. 3. The propylene / α-olefin copolymer according to claim 1, having an MFR of 0.1 to 30 g / 10 min at 230° C. under a load of 2.16 kg, as measured in accordance with ASTM D1238E.

4. The propylene / α-olefin copolymer according to any one of claims 1 to 3, wherein the α-olefin having 5 to 20 carbon atoms is at least one selected from the group consisting of 1-hexene, 1-octene, 1-decene, and 1-dodecene.

5. The propylene / α-olefin copolymer according to any one of claims 1 to 4, wherein the α-olefin having 5 to 20 carbon atoms is 1-octene.

6. An adhesive resin composition comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5.

7. A pellet comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

8. A molded article comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

9. A film comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

10. A sheet comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

11. A fiber comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

12. An injection-molded article comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

13. A blow molded article comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5, or the adhesive resin composition according to claim 6.

14. 7. An automobile part selected from an interior part and an exterior part, comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5 or the adhesive resin composition according to claim 6.

15. A cylindrical member selected from a pipe and a tube, comprising the propylene / α-olefin copolymer according to any one of claims 1 to 5 or the adhesive resin composition according to claim 6.

Citation Information

Patent Citations

  • Preparation of copolymer

    JP1978104686A

  • Propylene-1-butene copolymer and thermoplastic resin composition

    JP1999193309A

  • Propylene random copolymer, composition thereof and film and laminate made therefrom

    JP1999255834A

  • Transition-metal compound, catalyst for olefins polymerization, and preparation olefinic polymer

    JP2000256411A

  • Adhesive composition based on polypropylene

    JP2008524431A